2015
DOI: 10.3109/00365548.2014.985710
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and outcomes ofKlebsiella pneumoniaebacteraemia in Hong Kong

Abstract: The 30-day mortality and treatment cost of patients with K. pneumoniae bacteraemia were high in Hong Kong. Based upon the risk factors identified, infection control and treatment algorithms for K. pneumoniae bacteraemia in patients with malignancy or liver disease are highly warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 21 publications
1
14
0
1
Order By: Relevance
“…Studies reported from USA, Italy, Hong Kong and Korea also include data supporting our results (Pau et al 2015; Kang et al 2006; Capone et al 2013; Qureshi et al 2012). Qureshi et al have assumed that high mortality in BSI secondary to pneumonia was due to the higher severity of underlying disease and relative difficulty in controlling the source of infection in pneumonia compared with other sources (Qureshi et al 2012).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Studies reported from USA, Italy, Hong Kong and Korea also include data supporting our results (Pau et al 2015; Kang et al 2006; Capone et al 2013; Qureshi et al 2012). Qureshi et al have assumed that high mortality in BSI secondary to pneumonia was due to the higher severity of underlying disease and relative difficulty in controlling the source of infection in pneumonia compared with other sources (Qureshi et al 2012).…”
Section: Discussionsupporting
confidence: 90%
“…Presence of many adverse factors such as co-morbid diseases or negative clinical conditions adversely effecting survival may cancel the positive effects of appropriate use of empirical antibiotic therapy in lowering mortality rates. In similar studies it was reported that conformity of initial therapy with antibiogram test doesn’t lead to a change in survival rate of patients (Ben-David et al 2012; Pau et al 2015; Correa et al 2013; Qureshi et al 2012). …”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…After adjusting for multiple confounders, several parameters, such as probable source of infection from lung and high SOFA score, were associated with a higher crude 28-day mortality, as previously described [9, 41, 42]. For patients with SOFA scores above 7 at the onset of bacteremia, the 14-day mortality rate was shown to increase [43].…”
Section: Discussionmentioning
confidence: 68%